The contribution of proportional taxes and tax-free cash benefits to income redistribution over the period 2005-2018: Evidence from Italy - Stefano Boscolo (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Over the last two decades a growing interest in understanding what determines the redistributive role of tax-benefit systems has emerged worldwide. In the case of Italy, previous analyses were mainly focused on quantifying the contribution of marginal tax rates, deductions and tax credits to the redistributive capacity of personal income tax (PIT), while neglecting the effect on income redistribution of proportional taxes and income sources exempt from taxation such as tax-free cash benefits. This paper aims to fill this gap by applying two alternative Gini-based decomposition methodologies (Onrubia et al., 2014; Urban, 2014) to the redistributive effects of the Italian tax-benefit system over the period 2005-2018. The contribution of each tax-benefit instrument is quantified for several scenarios which diverge from each other in that they are representative of different degrees of extension of the tax-benefit system under examination.
Keywords: D3; H2; 330; tax-benefit system; progressive taxation; decomposition approach; redistribution; EUROMOD